Pengaruh Komunikasi dan Resolusi Konflik terhadap Family Ritual Dinner Time pada Orangtua yang memiliki Anak Berkuliah Sarjana - Edwin, Felix; Sanjaya, Ersa Lanang (Psychopreneur Journal, 2020)
This study aims to determine the effect of communication and conflict resolution on family rituals (dinner time) on parents who have children with college degrees. The total sample in this study amounted to 75 subjects. Dissemination of data using questionnaires distributed online and offline. Retrieval of data using Olsen's communication scale, Olsen's conflict resolution scale and Family Ritual Questionnaire (FRQ) family ritual. Data analysis uses multiple regression methods to determine the effect of communication and conflict resolution together on family dinner time rituals. And using simple linear regression to determine the effect of communication on family dinner time rituals and the effect of conflict resolution on family dinner time rituals. Results of multiple regression test analysis (r = 0,010; p = 0,696). Simple linear regression test results of communication on family rituals (r = 0,006; p =0,496). Simple linear regression test results conflict resolution to family ritual (r = 0,000; p =0,973). There is no influence of communication and conflict resolution on dinner time. There is no effect of communication on dinner time. There is no effect of conflict resolution on dinner time. So that in this study the major and minor hypotheses were rejected.